2021
DOI: 10.28948/ngumuh.879584
|View full text |Cite
|
Sign up to set email alerts
|

Shape modification of Ahmed body to reduce drag coefficient and determination of turbulence model

Abstract: In this study, the aerodynamic analysis of Ahmed body which is generic automobile model is performed to determine convenient turbulence model and reduce drag coefficient by modifying shape of model. For this purpose, Computational Fluid Dynamics (CFD) analysis is carried out using different turbulence models that are Spalart-Allmaras, (Shear Stress Transport) SST k-, Standard k-, Realizable k-, (Re-Normalisation Group) RNG k- turbulence models. The results are compared with experimental data that is availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The RNG k-ε turbulence method is suitable for ground vehicles since it gives more accurate results. The study of Şumnu [27] investigated different turbulence models to show which one is in good agreement with experimental results. Table 1 shows the drag coefficient values CD for five different turbulence models and their differences from the experimental result that is reported by Meile et al [31].…”
Section: Grid Independence and Cfd Validation Processmentioning
confidence: 75%
See 3 more Smart Citations
“…The RNG k-ε turbulence method is suitable for ground vehicles since it gives more accurate results. The study of Şumnu [27] investigated different turbulence models to show which one is in good agreement with experimental results. Table 1 shows the drag coefficient values CD for five different turbulence models and their differences from the experimental result that is reported by Meile et al [31].…”
Section: Grid Independence and Cfd Validation Processmentioning
confidence: 75%
“…It can be observed that the solution result of RNG k-ε turbulence model is close to the experimental value. In addition, the solution results are compared with both experimental data [31] and CFD results [27] to validate this study at 40 m/s and Reynolds number (length based on body) of 2.78×10 6 . Table 2 presents drag coefficient values for body without a control rod.…”
Section: Grid Independence and Cfd Validation Processmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, RNG (Re-Normalisation Group) k-ε turbulence model was used since this turbulence model simulates accurately flow field for this specified conditions [39]. This model is renormalized the Navier-Stokes equations and take into account smaller motion effect.…”
Section: Numeric Solutionmentioning
confidence: 99%